Preface: 3rd International Conference on Economic Management and Foreign Trade (EMFT 2024) - Bartlett, Gerald; Zhang, Jie (Transactions on Economics, Business and Management Research, 2024)
This proceeding consists of the peer-reviewed papers from the 2024 3rd International Conference on Economic Management and Foreign Trade (EMFT 2024), which was successfully held during September 28-29, 2024, in Edinburgh, United Kingdom. The main objective of EMFT 2024 is to provide a platform for researchers and practitioners from universities, academic institutions, and industries to meet and share cutting-edge developments in the areas of economic management, business statistics, market analysis, risk assessment, globalization, and foreign trade. This conference also provided an opportunity to exchange research evidence, innovative ideas, and the related issues. This proceeding will include presentations on the latest research areas. EMFT 2024 had gathered an excellent group of keynote speakers from around the globe on different topics such as: Household Behavior and Family Economics, Public Administration and Small Business Entrepreneurship, Labor Relations & Human Resource Management, Business Performance Management, Corporate Finance and Governance, Marketing Theory and Applications, and How Business Technology Platform Accelerates Your Innovation. Looking forward to seeing you again next year. Scientific Committee of EMFT 2024 Edinburgh, United Kingdom